2002
DOI: 10.1074/jbc.m107651200
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of the Metabolic Fate of Glucose in the Filamentous Fungus Trichoderma reesei Using Expressed Sequence Tag (EST) Analysis and cDNA Microarrays

Abstract: Despite the intense interest in the metabolic regulation and evolution of the ATP-producing pathways, the long standing question of why most multicellular microorganisms metabolize glucose by respiration rather than fermentation remains unanswered. One such microorganism is the cellulolytic fungus Trichoderma reesei (Hypocrea jecorina). Using EST analysis and cDNA microarrays, we find that in T. reesei expression of the genes encoding the enzymes of the tricarboxylic acid cycle and the proteins of the electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
98
1
11

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(122 citation statements)
references
References 26 publications
8
98
1
11
Order By: Relevance
“…In the case of soft-rot SSF, the acetic acid yield was as high as 11.3 g per 100 g of corn fiber ( Figure 5). Chambergo et al (19 ) reported the paralogous gene for the enzyme aldehyde dehydrogenase (ALD1 and ALD2) responsible for converting acetaldehyde to acetate. The authors also reported that these genes are highly expressed even under higher glucose concentration unlike S. cerevisiae.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of soft-rot SSF, the acetic acid yield was as high as 11.3 g per 100 g of corn fiber ( Figure 5). Chambergo et al (19 ) reported the paralogous gene for the enzyme aldehyde dehydrogenase (ALD1 and ALD2) responsible for converting acetaldehyde to acetate. The authors also reported that these genes are highly expressed even under higher glucose concentration unlike S. cerevisiae.…”
Section: Resultsmentioning
confidence: 99%
“…Fungi can be classified into Crabtree-negative and Crabtree-positive species based on their carbon utilization patterns. Crabtree-negative species up-regulate the pyruvate dehydrogenase complex in the presence of glucose, such that most of this carbon flows into the TCA cycle to generate biomass and CO 2 (Chambergo et al 2002;Maeda et al 2004;Xie et al 2004). Crabtree-positive fungi ferment most of the glucose to generate ethanol (Klein et al 1998), which is thought to promote the competitive ability of yeasts within polymicrobial microenvironments owing to the antiseptic nature of ethanol (Crabtree 1928).…”
Section: Carbon Assimilationmentioning
confidence: 99%
“…We are interested in metabolic engineering of the ascomycete Hypocrea jecorina (Trichoderma reesei) to increase the production of cellulase and other extracellular enzymes. The genome sequence of this fungus is now available (http://gsphere.lanl.gov/trire1/trire1 .home.html), as are cDNA sequences from mycelia grown on glucose or under cellulase-inducing conditions (5,7,10,24). However, knowledge of the genome-wide similarity of physiological profiles in various transformed strains and mutants often is needed to meaningfully interpret the gene expression data.…”
mentioning
confidence: 99%